Pengaruh Ekuitas Merek Dan Harga Terhadap Keputusan Pembelian Produk Mie Sedaap (Studi Pada Mahasiswa Fakultas Ekonomi Universitas Islam Majapahit) - Lia Amalia Damayanti; Hartono Hartono; Rini Armin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Company competition in marketing is not limited to the functional properties of the product, for example the ease of use of the product, but is related to brands that can offer a special image to their users. Products are described as commodities that are exchanged, whereas brands describe the specifications of its customers. Brand is one of the most important marketing factors. Brand is the identity of the product, the brand provides brief information about the product that consumers want. This study aims to determine the effect of Brand Equity and Price on purchasing decisions for Mie Sedaap products. The variables in this study are brand equity and price as the independent variable and purchase decision as the dependent variable. . This study used a quantitative method with a total sample of 96 respondents using a purposive sampling technique. The data collection method uses an online questionnaire. This study uses multiple linear regression analysis with data processing tools in the form of the IBM SPSS 26 program. The results of this study indicate that brand equity partially influences purchasing decisions (Sig 0.000 <0.05 and Tcount 12,984 > Ttable 1.989) and price partially influences purchasing decisions purchases (Sig 0.000 <0.05 and Tcount 5,899 > Ttable 1.989). Brand equity and price simultaneously influence purchasing decisions for sedaap noodle products (Sig 0.000 <0.05 and Fcount 249,423 > Ftable 3.09).